An Alternative to the Classical α‐Arylation: The Transfer of an Intact 2‐Iodoaryl from ArI(O2CCF3)21. Issue 42 (4th September 2014) - Jia, Zhiyu; Gálvez, Erik; Sebastián, Rosa María; Pleixats, Roser; Álvarez‐Larena, Ángel; Martin, Eddy; Vallribera, Adelina; Shafir, Alexandr
Abstract The α‐arylation of carbonyl compounds is generally accomplished under basic conditions, both under metal catalysis and via aryl transfer from the diaryl λ3‐iodanes. Here, we describe an alternative metal‐free α‐arylation using ArI(O2CCF3)2 as the source of a 2‐iodoaryl group. The reaction is applicable to activated ketones, such as α‐cyanoketones, and works with substituted aryliodanes. This formal CH functionalization reaction is thought to proceed through a [3, 3] rearrangement of an iodonium enolate. The final α‐(2‐iodoaryl)ketones are versatile synthetic building blocks.